Strategies for Sustainable Channel Relations in Mobile Telecom Sector - Heggde, Githa (Journal of Economics and Behavioral Studies, 2011)
The telecom sector in India largely comprises of wireless connections for phones. As of today, there are approximately 21 network providers in the country with about 7 per each circle, each offering competitive pricing to the consumers. The main objective of the study is to provide an accurate role for the company executive in developing channel relations. Further to this, the study explores the strategies which can sustain a good working relationship between the company and its channel members in the mobile telecom sector. The constructs identified for developing sustainable relationships were Setting distribution objectives, Channel design, Logistics, Image Building, Inventory management, Channel management, Payment & credit, Promotional assistance, Setting targets, Coverage frequency , Motivating channel members to perform. The sample selected contained distributors from the Mobile telecom sector and company executives/channel managers of leading telecom companies. Factor analysis and Friedman’s test was applied. The findings revealed a correlation in attitude between distributors and the executives. Motivating distributors was rated as the most important strategy by the company. The distributors felt that all channel partners needed to have positive attitude towards the channel while company executives felt that aggression made channel members perform effectively. Such findings will be of use to mobile telecom companies who are new entrants to the Indian market and to existing companies who plan to expand their coverage.